2006
DOI: 10.1093/nar/gkl133
|View full text |Cite
|
Sign up to set email alerts
|

Tests of rRNA hybridization to microarrays suggest that hybridization characteristics of oligonucleotide probes for species discrimination cannot be predicted

Abstract: Hybridization of rRNAs to microarrays is a promising approach for prokaryotic and eukaryotic species identification. Typically, the amount of bound target is measured by fluorescent intensity and it is assumed that the signal intensity is directly related to the target concentration. Using thirteen different eukaryotic LSU rRNA target sequences and 7693 short perfect match oligonucleotide probes, we have assessed current approaches for predicting signal intensities by comparing Gibbs free energy (ΔG°) calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
122
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(141 citation statements)
references
References 38 publications
15
122
4
Order By: Relevance
“…Again, in contrast to Goff et al (2005), we did not find a uniform hybridization for oligo variants that had been adjusted with respect to their melting temperature but rather a severe loss in sensitivity, and most notably, a variable influence of individual miRNA sequences. Therefore, as also described by Pozhitkov et al (2006) and Dimitrov and Zuker (2004), we doubt that there is, at least in complex assays, a simple consistency between Gibbs free energy and target sequence.…”
Section: Discussionmentioning
confidence: 93%
“…Again, in contrast to Goff et al (2005), we did not find a uniform hybridization for oligo variants that had been adjusted with respect to their melting temperature but rather a severe loss in sensitivity, and most notably, a variable influence of individual miRNA sequences. Therefore, as also described by Pozhitkov et al (2006) and Dimitrov and Zuker (2004), we doubt that there is, at least in complex assays, a simple consistency between Gibbs free energy and target sequence.…”
Section: Discussionmentioning
confidence: 93%
“…In silico approaches allow for partial prediction of the hybridization behavior of designed probes. However, it has become clear that the simple notion that short oligonucleotides with a mismatch (MM) should hybridize less efficiently than perfect-match (PM) probes is not always applicable [137]. It has been demonstrated that the hybridization intensity of MM probes can depend on the nucleotide type (i.e.…”
Section: Oligonucleotide Probesmentioning
confidence: 99%
“…More generally, there is a lack of a simple relationship between hybridizations of probe-target duplexes as inferred from signal intensity values and in silico predictions based on Gibbs free energies [137]. This does not apply as strictly for highdensity microarrays where the high level of redundancy accounts for the specificity of the signals nor for long oligonucleotide microarrays where inter-allele distinction is not required.…”
Section: Oligonucleotide Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low reproducibility and false-positive and false-negative signals with 16S rRNA gene-based arrays are partly accredited to bias caused by the characteristics of target molecules (8,17), and target-background interaction may be one of the main reasons for these phenomena. Poor statistical relationships between experimental and predicted signal intensities (from Gibbs free energy calculations) suggest that thermodynamic parameters between target-and-probe duplexes are not fully understood (26). Thus, an evaluation of the influence of dangling ends and surface-proximal tails on signal intensity and target-background interaction is needed in order to interpret the signal intensities from 16S rRNA gene-based diagnostic and microbial community analysis arrays.…”
mentioning
confidence: 99%